Education on the quality and halal system of meat products in Sayang Village, Jatinangor, Sumedang - Putri Widyanti Harlina; Nandi Sukri; Syamsul Huda (Universitas Muhammadiyah Magelang, 2022)
Meat and processed meat products are important sources of nutrients for humans because they contain proteins, lipids, minerals, and vitamins. However, the majority of residents in Sayang Village, Jatinangor, Sumedang lack of knowledge to understand the type of meat that is halal, safe, and high quality. This program aims to educate community of the halal systems and product quality of meat. The method used is presentations, discussions, and training about how to make sausages and shred meat through videos. The outcomes of the program showed that the PKK team in Sayang Village, learned more about the quality of meat as well as proper methods for processing and storing meat so that nutrition is preserved. Additionally, partners can keep raising awareness of the value of the fresh meat quality and halal products that will be made into high-protein foods for family.